Similarity coefficient-based cell formation method considering operation sequence with repeated operations. Issue 6 (3rd June 2022) - Wu, Lang; Shen, Yifan; Niu, Ben; Li, Li; Yang, Congcong; Feng, Yuanyue
Abstract : Cell formation is a crucial problem in the design of cellular manufacturing systems and has a decisive effect on productivity and cost. The similarity coefficient method is the most widely used to solve this problem because of its flexibility and computational efficiency. Although various similarity coefficient methods have been developed in the literature, few of these methods consider the factor of operation sequence with repeated operations, which may cause more material intercell movements. To fill this research gap, this study presents an improved similarity coefficient method for designing machine groups in the first stage. Subsequently, a modified part assignment strategy is proposed for forming cells to achieve a higher compatibility with the improved similarity coefficient method. Finally, problems from previous studies are employed to demonstrate the performance of the proposed method. Comparison results testify that the proposed method is sensitive and efficient for solving the cell formation problem.